PERENCANAAN PENGGANTIAN KONSTRUKSI DARI FLEXIBLE KE RIGID APRONTAXIWAY MENUJU PARKINGSTAND 1 (SATU) DI BANDAR UDARA INTERNASIONAL AHMAD YANI SEMARANG - Alfian Nur Bagaskoro; Sukamto; Luky Surachman (Politeknik Penerbangan Indonesia Curug, 2017)
The Ahmad yani International Airport Semarang have an apron with an area of 29.032,00 m2 With Rigid and Flexible construction. Rigid construction is locate at parkingstand with a total of 8 unit while the flexible construction located in aprontaxiway. Due to frequently damage in aprontaxiway, there is need a change from flexible to rigid construction. Choose the biggest aircraft, counting the pavement’s thick that will created and choose the joint pavement refer to the KP 262 year 2017, FAA AC 150 /5320 6D and FAA AC 150/5320 6E rules. The critical Aircraft is B 737-900 ER, thick of pavement is 68, 75cm and construction joint using dowel with length of 51cm, 4mm diameter and distance between dowel is 46cm with PCN 57 R/C/X/T will used in plan to change aprontaxiway to parkingstand construction at Ahmad Yani International Airport, semarang